Ko-Produksi Pengetahuan sebagai Basis Kesadaran Perilaku dalam Pelayanan Sanitasi di Indonesia: Kasus Desa Sumberdawesari, Kabupaten Pasuruan, Jawa Timur - Suyadnya, I Wayan; Novenanto, Anton; Tirtayani, Luh Ayu (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
This study is focused on the change in new behaviour and routines on the issues of safe water and sanitation in Indonesia. The aim of this study is to explain the deconstruction of people's consciousness and societal knowledge on wastewater treatment plant (IPAL) facilities and the resulting behavioural change. By positioning programmes of safe water, sanitation, and the local value of healthy living as the “life projects”, this article attempts to re-examine the position of local communities in this project. Life projects are programmes that adhere to the local histories of communities in perceiving ‘development’. Life projects are premised on densely and uniquely woven 'threads' of landscapes, memory, expectations, and desire. In this regard, this article tries to disclose the participation of local communities in planning, managing and integrating local values and global visions of proper sanitation development programs in their villages. This study was a micro one conducted at Sumberdawesari village, in Pasuruan, East Java. Sumberdawesari is one of the IWINS-USAID’s pilot projects of the communal IPAL programme. This research utilizes the life history approach with the data collection techniques of observation, biography, focus group discussions, and in-depth interviews. The nature of this study focuses on the desire to share information about low-level experiences of local communities regarding the availability and the sustainable management of water and sanitation toward a healthy and self-reliance settlement. This research finds the increased awareness of the population in implementing sanitation development programs at the level of habitus, individual, household, community, and social structure through the dimensions of contextual, managerial and technical knowledge.